Osseointegration of Antimicrobial Acrylic Bone Cements Modified with Graphene Oxide and Chitosan (2020)
Acrylic bone cement (ABC) is one of the most used materials in orthopedic surgery, mainly for the fixation of orthopedic implants to the bone. However, ABCs usually present lack of biological activity and osseointegration capacity that leads to loosening of the prosthesis. This work reports the effect of introducing graphene oxide (GO) and chitosan (CS), separately or together, in the ABC formulation on setting performance, mechanical behavior, and biological properties. Introduction of both CS and GO to the ABC decreased the maximum temperature by 21% and increased the antibacterial activity against Escherichia coli by 87%, while introduction of only CS decreased bending strength by 32%. The results of cell viability and cell adhesion tests showed in vitro biocompatibility. The in vivo response was investigated using both subdermal and bone parietal implantations in Wistar rats. Modified ABCs showed absence of immune response, as confirmed by a normal inflammatory response in Wistar rat subdermal implantation. The results of the parietal bone implantation showed that the addition of CS and GO together allowed a near total healing bone–cement interface, as observed in the micrographic analysis. The overall results support the great potential of the modified ABCs for application in orthopedic surgery mainly in those cases where osseointegration is required.